Srečko Kosovel pri Italijanih - Jan, Zoltan (Primerjalna književnost, 2000)
The reception of Srečko Kosovel in Italy. The reception of the Slovene poet Srečko Kosovel in Italy is rather interesting, as it reveals a number of curious facts, one of which is that interest in Kosovel as a poet was restricted to a small, local area and has for a while been confined mainly to the regions around Trieste and partly Gorizia. More recently recognition and appreciation of his writing has been spreading to the rest of Italy. It is important that he has been accepted in the intellectual sphere of some prominent Italian authors, who spontaneously pay regard to Srečko Kosovel on various occasions and respect him as an important poet.
Keywords: Kosovel, Srečko, 1904-1926; Slovene literature; slovenska književnost; literarne študije; prevodi